General Diagnostics and Surgical Treatment of Complicated Forms of Liver Echinococcosis - Akhmadova M. A; Nurov J. R (Research Parks Publishing LLC, 2021)
To evaluate approaches to surgical treatment of complicated forms of liver echinococcosis. From 2018 to 2021, surgical treatment of liver echinococcosis was performed in 197 patients, of which 157 (79.7%) had primary echinococcosis, and 40 (20.3%) had recurrent echinococcosis. ... The data on the treatment of 46 (22.8%) patients with complicated echinococcosis are analyzed. 4 patients had associated complications. Among the complicated forms of liver echinococcosis, cyst suppuration is most common. Among the complicated forms of liver echinococcosis, cyst suppuration is most common. Patients with complicated liver echinococcosis should be operated in a specialized institution with modern diagnostic and therapeutic equipment, highly qualified specialists.